From promises to action: Analyzing global commitments on food security and diets since 2015 - Zorbas, Christina; Resnick, Danielle; Jones, Eleanor; Suri, Shoba; Iruhiriye, Elyse; Headey, Derek D.; Martin, Will; Vos, Rob; Arndt, Channing; Menon, Purnima (International Food Policy Research Institute, 2024)
Achieving Sustainable Development Goal 2 (SDG 2), Zero Hunger, by 2030 is in jeopardy due to slowing and unequal economic growth, climate shocks, the COVID-19 pandemic, conflict, lackluster efforts toward investing in food system sustainability and agricultural productivity growth, and persistent barriers to open food trade. Nevertheless, numerous commitments to achieving SDG 2 have been repeatedly expressed by Heads of State and Ministers at diverse global meetings since the SDGs became a focus in 2015. To identify the intensity and degree of convergence of commitments that national governments have collectively made to realizing SDG 2, this paper provides a qualitative assessment of statements from more than 68 global meetings and 107 intergovernmental commitment documents since 2015. Analyzing these commitments against seven critical factors necessary for impact at scale, we find that stated intentions to solve the global food security and hunger challenge have become more pronounced at global meetings over time, especially in the wake of the crises. However, the intent to act is not consistently matched by commitments to specific actions that could help accelerate reductions in hunger. For instance, while increased financing is often recognized as a priority to reach SDG 2, few commitments in global fora relate to detailed costing of required investments. Similarly, many commitment statements lack specificity regarding what and how policy interventions should be scaled up for greater action on SDG 2 or the ways to enhance different stakeholders’ capacities to implement them. While horizontal coherence was mentioned across most global fora, it was only present in about half of the commitment statements, with even less recognition of the necessity for vertical coherence from global to local levels. Despite global acknowledgement of the importance of accountability and monitoring, usually by way of progress reports, we find few consequences for governments that do not act on commitments made in global fora. We discuss the implications of these findings and offer recommendations for how to strengthen the commitment-making process to help accelerate actions that can reduce food insecurity and hunger and augment the legitimacy of global meetings. This work can inform the policy advocacy community focused on SDG 2 and those engaged in catalyzing and supporting intergovernmental action on other SDGs. Our findings reiterate the importance of attention to global governance and the political economy of global meetings—which is necessary to strengthen our focus on delivering outcomes that put the world on a path that brings the solution to the problems of global hunger and food insecurity within reach.